2020
DOI: 10.3390/cells9112344
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of G2019S and R1441C LRRK2 Mutations on LRRK2 and Rab10 Phosphorylations in Mouse Tissues

Abstract: Mutations in LRRK2 cause familial Parkinson’s disease and common variants increase disease risk. LRRK2 kinase activity and cellular localization are tightly regulated by phosphorylation of key residues, primarily Ser1292 and Ser935, which impacts downstream phosphorylation of its substrates, among which Rab10. A comprehensive characterization of LRRK2 activity and phosphorylation in brain as a function of age and mutations is missing. Here, we monitored Ser935 and Ser1292 phosphorylation in midbrain, striatum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 56 publications
13
32
0
Order By: Relevance
“…Interestingly, in neutrophils from carriers of the less common R1441G mutation in LRRK2, a significant increase in pT73-Rab10 is detected in comparison to healthy controls, irrespective of disease status 12 . This is consistent with findings reported in transgenic mice expressing R1441C or G2019S, where a robust increase in Rab10 phosphorylation was observed in R14411C but not G2019S mice 13 . Most recently, using a proprietary antibody raised against pT73-Rab10, Wang and colleagues reported that phosphorylated Rab10 levels, normalized to total LRRK2, are increased in PBMCs of affected carriers of the G2019S mutation 8 and are reduced in cells treated ex vivo with LRRK2 kinase inhibitors.…”
supporting
confidence: 93%
“…Interestingly, in neutrophils from carriers of the less common R1441G mutation in LRRK2, a significant increase in pT73-Rab10 is detected in comparison to healthy controls, irrespective of disease status 12 . This is consistent with findings reported in transgenic mice expressing R1441C or G2019S, where a robust increase in Rab10 phosphorylation was observed in R14411C but not G2019S mice 13 . Most recently, using a proprietary antibody raised against pT73-Rab10, Wang and colleagues reported that phosphorylated Rab10 levels, normalized to total LRRK2, are increased in PBMCs of affected carriers of the G2019S mutation 8 and are reduced in cells treated ex vivo with LRRK2 kinase inhibitors.…”
supporting
confidence: 93%
“…For example, G2019S and I2020T, both located at the kinase domain, increase the phosphorylation activity of LRRK2 137,138 , most likely through the stabilization of its active status 139 . Alternatively, mutations at the ROC-COR domain have a direct effect on ROC by slowing GTP hydrolysis, which affects cellular phosphorylation of LRRK2 substrates by impairing LRRK2 recruitment to signaling compartments or by improper interactions with ROC binding partners 132,[140][141][142][143] .…”
Section: -3-3 Roles In Parkinson's Diseasementioning
confidence: 99%
“…Our study suggests absence of astrocyte degeneration or atrophy, since the levels of the cytosolic astrocyte marker GS were not perturbed in the context of disease. Accordingly, the presence of astrocyte reactivity has been reported in different transgenic mice overexpressing the LRRK2 G2019S kinase [34, 91].…”
Section: Discussionmentioning
confidence: 99%